STRATEGI KEPEMIMPINAN KEPALA DESA DALAM MEMBANGUN TOLERANSI ANTARUMAT BERAGAMA DI DESA BANDAR KLIPPA - Ramadhan, Mohammad Rizky; Rubino, Rubino (IAIN PONOROGO, 2026)
Tolerance between religious communities is crucial for creating harmonious social relations in a pluralistic society. However, religious diversity also has the potential to lead to conflict due to differences in identity and belief. In contrast, Bandar Klippa Village, as a multireligious village, exhibits a relatively harmonious social life with minimal conflict. This study aims to analyze the state of interreligious tolerance, identify underlying factors, and examine the village head's leadership strategies in building tolerance. The study employed a qualitative approach with a single case study design. Data were obtained through interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model. The results indicate that interreligious tolerance in Bandar Klippa Village is relatively good, reflected in interfaith social interactions, joint participation in community activities, and conflict resolution through deliberation. This condition is supported by the values of togetherness, the intensity of social interactions, and the village head's inclusive leadership strategy through interfaith dialogue, active attendance at religious activities, strengthening social activities, and the involvement of interfaith representatives in the village's social structure. Implicitly, this research emphasizes the importance of inclusive and participatory local leadership in maintaining social stability in multicultural societies and can serve as a reference for village governance practices and the development of local leadership studies.